Pengaruh jenis penutup botol kultur terhadap pertumbuhan planlet kelapa sawit (Elaeis guineensis Jacq.) Effect of different culture vessel closures on the growth of oil palm (Elaeis guineensis Jacq.) plantlets - Masna Maya SINTA; Imron RIYADI; . UMARYONO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2011)
AbstractMicroenvironment inside the culture vessel such astemperature, light intensity, relative humidity, and aerationaffect growth and development of plantlets. This experimentwas conducted to determine the effect of different culturevessel closures on microenvironmental conditions inside thevessel and on growth of plantlets of oil palm. Shoots of oilpalm derived from somatic embryos were cultured on DFmedium for eight weeks in transparent culture bottlescovered with five different vessel closures e.i. screw cap withplastic wrap, screw cap, plastic wrap, aluminum foil, andautoclavable plastic. The culture vessels were placed in theculture room with light intensity 20 µmol/m 2 /sec for 12 hoursphotoperiod, at room temperature 26°C. Parametersobserved on plantlet growth were shoot height, biomass freshweight, leaf number, and leaf color grade, while onmicroenvironment were temperature and light intensity. Atthe end of experiment, the volume and fresh weight of theremaining medium were measured to determine evaporationrate of each treatment. Results show that the use of differentculture vessel closures affected the microenvironment insidethe vessel, the volume of the remaining medium, and thegrowth of the plantlets. The closure increased thetemperature by 1.6 – 2.6°C and decreased the light intensityby 1.7 – 8.7 µmol/m 2 /sec inside the culture vessels dependson the culture vessel closures. Culture vessels with aluminumfoil closure had the lowest temperature (28.9°C) and thelowest light intensity (10.8 µmol/m 2 /sec) gave the best resultin the growth of the plantlets. Better plantlets growth wasalso observed in the culture vessel with autoclavable plasticclosure that less expensive, therefore it can be used as analternative vessel closure for the growth of oil palm plantlets.AbstrakLingkungan mikro di dalam botol kultur seperti suhu,intensitas cahaya, kelembaban nisbi dan aerasi mem-pengaruhi pertumbuhan dan perkembangan planlet.Penelitian ini dilakukan untuk mengetahui pengaruhpenggunaan penutup botol kultur yang berbeda terhadapkondisi lingkungan mikro di dalam botol kultur danpertumbuhan planlet kelapa sawit. Planlet kelapa sawit asalembrio somatik dikulturkan dalam botol kultur bening berisimedium DF selama delapan minggu dan ditutup mengguna-kan lima jenis penutup botol yang berbeda yaitu tutup ulirdengan plastik wrap, tutup ulir, plastik wrap, aluminium foildan plastik tahan diautoklaf. Kultur diletakkan dalam ruangkultur, di bawah lampu TL dengan intensitas cahaya20 µmol/m 2 /detik dan suhu ruang 26 o C. Parameterpertumbuhan planlet yang diamati adalah tinggi planlet,bobot basah, jumlah daun dan kelas warna daun, sedangkanlingkungan mikro adalah suhu dan intensitas cahaya. Padaakhir eksperimen, volume dan bobot basah medium yangtersisa diukur untuk mengetahui tingkat penguapan padasetiap perlakuan. Hasil penelitian menunjukkan bahwapenggunaan penutup botol yang berbeda berpengaruhterhadap lingkungan mikro, volume medium tersisa dalambotol kultur dan pertumbuhan planlet. Penutup botolmeningkatkan suhu 1,6 – 2,6 o C dan menurunkan intensitascahaya 1,7 – 8,7 µmol/m 2 /detik di dalam botol tergantungpada jenis penutup botol yang digunakan. Botol kulturdengan penutup berbahan aluminium foil mempunyaiintensitas cahaya terendah (10,8 µmol/m 2 /detik) dan suhuterendah (28,9 o C) memberikan hasil terbaik pada pembesaranplanlet kelapa sawit. Pertumbuhan planlet yang baik jugaterdapat pada botol kultur dengan penutup plastik tahandiautoklaf yang lebih murah, sehingga penutup ini dapatdigunakan sebagai pilihan untuk pembesaran planlet kelapasawit.